Nickel-catalyzed arylative cyclizations enabled by reversible alkenylnickel E/Z isomerization - Yap, Connor (2019)
Herein is described the first enantioselective intramolecular allylation of alkenylnickel nucleophiles. These reactions are initiated by the addition of an arylboronic acid across an alkyne, followed by cyclization of the resulting alkenylnickel species onto an allylic phosphate. The reversible E/Z isomerization of the alkenylnickel species is essential for the success of the reactions.